To Assess Dentist Knowledge About Lipid Treatment of Local Anesthetic Systemic Toxicity - Nitin Bhagat1, Rohit Sharma2, Siddharth Rawat2, Sheikh Abrar3,Singh Priyanka Jaiprakash3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The present study was conducted to assess dentist knowledge about lipid treatment of local anesthetic systemic toxicity. Materials & Method: This study was conducted on 260 dentists of both genders. All were provided with a questionnaire. Information regarding LAST, signs of LAST they encountered and treatments for LAST, the length of professional experience, training on local anesthesia, LAs used most often, side effects seen most often were recorded. Results: Out of 260 dentists, 140 were male and 120 were female. 0-5 years experience was seen in 20, 5-10 in 70, 10-15 years in 50 and >15 years in 120 dentists. The difference was significant (P< 0.05). 62% had no idea of lipid treatment, 23% had heard but did not have enough knowledge of it, 13% had read an article about lipid treatment and 2% knew how to use lipid treatment. The difference was significant (P< 0.05). 85% had never seen LA toxicity, 12% had not use lipid treatment in local anesthesia toxicity and 3% had use lipid treatment in local anesthesia toxicity. The difference was significant (P< 0.05). Conclusion: Authors suggested that dentists must be aware of LA toxicity and knowledge of how to treat it.